MENGGALI MAKNA PEMAAFAN HAKIM BAGI ANAK MELALUI RATIO LEGIS PASAL 70 UNDANG-UNDANG SISTEM PERADILAN PIDANA ANAK - Aprilianda, Nurini (Universitas Brawijaya, 2023)
This research aims to discover the meaning of pardon given by the judge as governed in Article 70 of Law Number 11 of 2012 concerning the Judicial System of Juvenile Crime (henceforth referred to as Juvenile Law). The absence of further elucidation of Article 70 of Juvenile Law interrupts the settlement of the case handled by judges. Therefore, the value that the pardon carries in the Article needs to be further examined. This normative research uses statutory and conceptual approaches. The result shows that indicating that punishment, referring to Article 70 of Juvenile Law and imposed on a child, is given as the last resort that should take into account human values and the justice for children, philosophical bases, the values of Pancasila and the 1945 Constitution of the Republic of Indonesia with the principle of child protection referred to as a benchmark.